Analysis of the Causes of a Different Approach to the Inflow of Immigrants in the European Union Member States - Tendera-Właszczuk, Helena (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2017)
The influx of illegal immigration to the European Union has grown rapidly over the past few years. Member States’ official stances and policies differ considerably as to whether to accept or reject refugees and illegal immigrants. Using a quantitative analysis, the article examines the causes of the different approaches to immigration to the EU Member States. It provides a general overview of the demographic forecasts until 2080 and suggests two new indicators to explain the acceptance (or rejection) of foreigners. It follows from the considerations that quantitative indicators are insufficient in determining whether to have a positive or negative position with regard to accepting immigrants to EU Member States.